MON-708 Characterizing DNA Methylation Signatures in Adipose Tissue from Metabolic Impaired Asymptomatic Individuals - Escalante-Araiza, Fabiola (J Endocr Soc, 2020)
Obesity remains as a global epidemic characterized by progressive metabolic dysregulation in glucose homeostasis. Along with a genetic association in the development of T2D, epigenetic regulation has been suggested as a significant contributor in altered gene expression. Recent studies have described DNA methylation changes in insulin-sensitive tissues involved in T2D pathogenesis, however epigenetic dynamics on early stages to metabolic alterations is still unclear. We investigated potential DNA methylation signatures in 34 asymptomatic individuals from the GEMM family study. We compared differentially methylated CpG sites (DMC: B value>0 and delta Beta >|10%|; Infinium EPIC array) from subcutaneous adipose tissue (SCAT) in different groups of individuals according to BMI (kg/m(2)) and HbA1c (%) levels as follow: Group A Control (C): n=9, 22.0±1.9 kg/m(2), 4.8±0.3%; Group B Overweight (OW) with normal HbA1c: n=6, 27.8±1.6 kg/m(2), 5±0.2%; Group C Obese (OB) with normal HbA1c: n=6, 34.6±4.2 kg/m(2), 5.2±0.2%; Group D Prediabetes (PD): n=7, 31.1±5.7 kg/m(2), 5.9±0.2% and Group E T2D: n=6, 30.6±7.3 kg/m(2), 7.2±0.9%. We found 43 overlapping genes with shared pathways in all groups, mainly those related to metabolism and adipogenesis. We also documented particular altered methylated genes, in each group (OW: 386, OB:1005, PD:76 and T2D:189). Pathway enrichment analysis in OB and T2D was mainly related to glucose metabolism, while in OW and PD was NOTCH signaling. All groups displayed a consistent hypermethylation in RARA, ESR1 and NCOR2, well known genes involved in lipid metabolism. Additionally, we describe for the first time, a progression toward hypomethylation in ARHGAP15 and MTAP, related with an impaired metabolic status. Otherwise, analysis of overlapping CpG sites revealed a consistently hypermethylated state in OW (86.42%), OB (86.48%) and PD (51.72%), in contrast with the hypomethylation state (56.3%) observed in the T2D group, previously observed elsewhere (1). In conclusion, comparison of methylation in SCAT obtained from OW, OB, PD and T2D individuals, display potential pathways and DMC signatures specific in each group. Common novel overlapping genes in global DNA methylation profiles of SCAT, were also observed. Reference: (1) Barajas-Olmos et al., BMC Med Genet. 2018 Feb 21;19(1):1-8. Nothing to Disclose: FE, FB, AM, EH, GEMM, ER, RB, LO.